Kuuk, Skrap, and the Resistance Vernacular - Ålvik, Jon Mikkel Broch (Nordlit, 2020)
How are gendered identities enabled, contested, and performed through Nordic popular music? Building on relevant approaches in popular music analysis, this article offers an investigation into the function/s of language and musical style in enabling and engendering agency and subjectivity via two case studies in Norwegian popular music.Gender and language are crucial factors in this. In a global context of popular music, bands and artists who choose to sing in their local language may be seen to take up marginal positions compared to artists who choose to sing in English, as the choice of language would naturally limit their audience. I argue that this overlooks the efficacy of using one’s local language to express points of view that are relevant on a local level; what is more, it overlooks the possibility of subverting globalized trends and using these to one’s own ends.In this article, I offer close readings of Norwegian-language albums by two all-female groups: the hip-hop duo Kuuk (Live fra Blitz) and the electronica duo Skrap (Atlantis). Applying Russell A. Potter’s (1995) concept of the ‘resistance vernacular’ as it has been expanded and operationalized by Tony Mitchell (2004), I contend that the bands’ use of their local language opens their music to a broader set of possibilities when it comes to subverting gender and genre norms at the same time as it enhances the music’s political potential.Working in discernible genres enables both bands to create music that expresses a feminist stance; in the case of Kuuk, deconstructing and subverting expectations of gendered behaviour through parodying hip-hop misogyny, and in the case of Skrap, drawing on strategic naïvety to steer clear of gender stereotypes.
Keywords: Popular music; Resistance; Language; Gender